Levels of depression, anxiety, and stress of PPLP Gorontalo karate and pencak silat athletes facing the national sports week qualification round - Hartono Hadjarati; Meri Haryani; Nurkhoiroh Nurkhoiroh (Universitas Negeri Malang, 2023)
Background: Stress and anxiety are becoming more common and prone to occur among athletes, especially martial arts athletes in the pencak silat and karate, facing national or international level matches. One example of such a problem is during the National Sports Week Prequalification round. This condition blames the pressure from internal and external aspects (e.g., coaches) to win first place-the urgency to win the tournament results in an intensive training program. Karate and pencak silat are different martial arts, meaning that each has different stress, anxiety, and depression. Objective: The objective of this study is to explore the level of stress, anxiety, and depression between the two martial arts. Methods: This quantitative study relied on a comparative approach. As many as 35 Gorontalo PPLP athletes from Karate and Pencak silat were involved as the research population. Some were selected as the sample using the total sampling method. All data were retrieved using the depression anxiety and stress scale (DASS-42) by Lovibond and Lovibond. This questionnaire has been adapted into the Indonesian language. After the descriptive analysis of the data, the homogeneity and normality tests were performed as the data analysis prerequisite. Results: Following this test was a t-test to examine the hypothesis. The research results show no significant differences in the stress and anxiety levels of karate and pencak silat athletes. Interestingly, there are significant differences in the depression levels of karate athletes and pencak silat athletes. Conclusion: Reducing stress, anxiety, and depression in athletes is imperative to support martial arts performance.